Comparison of the level of physical and sport activity involvement among pupils and universities students in Lithuania - Podolskyte, Gabija (Πανεπιστήμιο Πελοποννήσου, 2024)
The thesis examines the level of P&SA involvement of Lithuanian schoolchildren and students and its differences according to age groups. Also, this work aims to find the reasons why young people do not fulfill WHO’s recommendations on PA through various forms of P&SA. The research sample consisted of 351 respondents. Respondents are divided into three age groups: a) 13-15 years, b) 16-18 years, and c) 19-23 years old. Distribution of the study sample by age groups: a) 13-15 years – 136 respondents, b) 16-18 years – 103 respondents, c) 19-23 years old – 112 respondents. For the study, the method of a questionnaire classified as a quantitative data collection strategy was chosen. Based on the literature read, a questionnaire was prepared, which allowed not only to calculation the level of involvement of Lithuanian schoolchildren and students in P&SA but also to discover the reasons that determine the involvement or, on the contrary, non-involvement of young people in P&SA. After conducting the research, main conclusions are presented. 19-23 age group students get involved in P&SA activities the least compared to the 13-15 and 16-18 age groups and it is influenced by several internal and external aspects. Although students are generally aware of the importance of P&SA and its benefits for emotional and physical health, the reasons why young people refuse to participate in P&SA are much broader than just their perceptions. However, to see the whole picture of the country's P&SA involvement, future forecasts, and visions, it is significant to look at this issue from another perspective. Therefore, suggestions for other studies are given to conduct a qualitative study. The research group of the study could be not students but institutions responsible for education or educators. Whose answers could also contribute significantly to the better involvement of Lithuanian youth in P&SA.
Keywords: Φυσική αγωγή και εκπαίδευση - Έρευνα - Μεθοδολογία - Λιθουανία; Φυσική αγωγή - Έρευνα - Λιθουανία; Φυσική κατάσταση - Μετρήσεις; Άσκηση - Μετρήσεις; Άσκηση - Απόψεις υγείας - Έρευνα - Μεθοδολογία; Προαγωγή υγείας; Φυσική κατάσταση - Απόψεις υγείας; Physical education and training - Research - Methodology - Lithuania; Physical education - Research - Lithuania; Physical fitness - Measurement; Exercise - Measurement; Exercise - Health aspects - Research - Methodology; Health promotion; Physical fitness - Health aspects; Physical activity; Sport; Youth; Involvement